Application of radiative fluid dynamics scaled from the laboratory to astrophysics - Cross, J (2015)
Since its inception, the laser has found numerous applications beyond anything that could have been foreseen at its creation. With scientific and technological advancements, lasers are now capable of delivering a large amount of energy in very short timescales: giving us the ability to form interesting states of matter such as plasmas. As it became possible to create such material on earth, it made sense to consider applications this could be used for. Astrophysics typically uses a combination of observation, theory and simulation in order to further our understanding of the cosmos. The ability of the laser to create matter in similar states to those found in many astrophysical phenomena opened up a complimentary research area: laboratory astrophysics. The thesis begins by describing the basic physics underlying plasmas and fluid theory, before extending this to a non-dimensional form in the ideal hydrodynamic case: the so-called Euler equations. A novel way of including non-ideal terms, such as radiative, magnetic and quantum effects, is shown. Restrictions, and guidelines, to creating suitable lab experiments are drawn from this, and an experimental analogue of a polar star system is described. The design, simulation, execution and analysis of the experiment, led by the author, is given. Good agreement is found between experimental results, simulations and astrophysical theory. An experimentally measurable quantity, the structure factor, is then derived from hydrodynamics, and extended to include radiative effects, using the framework introduced in the first section. The impact of including such effects is discussed and determined to be non-negligible. Finally, we conclude by drawing together all these areas.